Women Prospects and Challenges in the Nigerian Politics: A Study of Yola North Local Government - Ibrahim, Sanusi; Maija, Abdullahi M. (Kashere Journal of Politics and International Relations, 2025)
This paper examines the participation of women in politics in Adamawa State, Nigeria, highlighting the challenges and opportunities that shape their political engagement. Despite constituting a significant proportion of the population, women remain underrepresented in political offices and decision-making positions. The study identifies cultural and social barriers, limited education and economic empowerment, political party dynamics, and violence and intimidation as major obstacles to women's political participation. However, constitutional provisions, gender activism, political will, and international support offer opportunities for increasing women's political representation and empowerment. A descriptive survey research methodology was adopted for this study. This approach primarily uses a questionnaire as the instrument for the data collection in the study. However, the study adopts interviews for more detailed information on the phenomenon. The population of the study include women primary in politics, People Democratic Party (PDP) and Progressive Congress (APC) party officials, the Independent National Electoral Commission (INEC) staff at the INEC headquarters in Yola North, and the number of electorates. Moreover, the study adopted the probability sample technique for data collection, and it used the following formula: [ɛ= ()] to find out the number of samples required for the study and the sample size was 284 respondents: The paper recommends gender-sensitive policies, political party reforms, voter education, and economic empowerment to address the challenges and harness the opportunities. By promoting women's political participation, Adamawa State can enhance democratic governance, development, and gender equality.